for these you need to rearrange the equations and do substitutions.
#3 = if x+y=5 then you know x = 5-y
now substitute that equation for x in the 2nd one so x + 2y = 8 becomes
5-y + 2y = 8 2y - y becomes 1y which becomes y then subtract 5 from each side to get y =3
now replace y with 3 in the first equation x = 5-3 so x = 2
so (2,3) is the answer
same type of work for #4
2x-y=6 ,S0 y = 2X+6
so now you have 4x+2(2x+6)=-4
that becomes 4x +4x+12 = -4
8x+8 = 1, x =1
y = 2(1)-6 = -4
so answer is (1,-4)
Answer:
43
Step-by-step explanation:
g(x)=4x+3
plug in 10
g(10)= 4(10)+3
= 40+3
= 43
Answer:d
Step-by-step explanation:
Answer:
24x4 24 divided by 4 24+ 4 it should be one of these hope this helps
Step-by-step explanation: